Coastal flooding and frontline health care services: challenges for flood risk resilience in the English health care system. Issue 4 (October 2019) - Landeg, Owen; Whitman, Geoff; Walker-Springett, Kate; Butler, Catherine; Bone, Angie; Kovats, Sari
Objectives: Our objective was to assess the health care system impacts associated with the December 2013 east coast flooding in Boston, Lincolnshire, in order to gain an insight into the capacity of the health care sector to respond to high-impact weather. Methods: Semistructured interviews were held with regional strategic decision makers and local service managers within 1 km of the recorded flood outline to ascertain their experiences, views and reflections concerning the event and its associated health impacts and disruption to health care services. A snowballing sampling technique was used to ensure the study had participants across a broad range of expertise. Interviews were recorded and transcribed verbatim, and data analysis was preformed using NVivo (v10) to apply a thematic coding and develop a framework of ideas. Results: The results of this case study provide a vital insight into the health care disruption caused by flooding. All sectors of the health care system suffered disruption, which placed a strain on the whole system and reduced the capacity of the sector to respond to the health consequences of flooding and delivering routine health care. The formal recovery phase in Lincolnshire was stood-down on 4th February 2014. The results of this work indicate limitations in preparedness of the health care system for the reasonable worse-case scenario for an east coast surge event. Conclusions: The health care sector appears to have limited capacity to respond to weather-related impacts and is therefore unprepared for the risks associated with a future changing climate. Further work is required to ensure that the health care system continues to review and learn from such events to increase climate resilience.